2009
DOI: 10.1111/j.1751-553x.2007.00997.x
|View full text |Cite
|
Sign up to set email alerts
|

Selected Stro‐1‐enriched bone marrow stromal cells display a major suppressive effect on lymphocyte proliferation

Abstract: Summary Mesenchymal stem cells (MSCs) have an immunosuppressive effect and can inhibit the proliferation of alloreactive T cells in vitro and in vivo. Cotransplantation of MSCs and hematopoietic stem cells (HSCs) from HLA‐identical siblings has been shown to reduce the incidence of acute graft‐vs.‐host disease. MSCs are heterogeneous and data on the inhibitory effects of different MSC subsets are lacking. The antigen Stro1 is a marker for a pure primitive MSC subset. We investigated whether Stro‐1‐enriched ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(59 citation statements)
references
References 41 publications
4
53
0
1
Order By: Relevance
“…Although Nasef et al suggest that a purified Stro-1-enriched population augment the suppressive effect in allogeneic transplantation, Murphy et al showed that allogeneic endometrial regenerative cells (ERC or menstrual blood mesenchymal stem cells), that are Stro-1 negative, were efficient for the treatment of critical limb ischemia in rats [34,32]. In accordance to recent studies in human endometrium, htMSCs are also Stro1 negative [35].…”
Section: Multilineage Differentiation In Vitromentioning
confidence: 65%
“…Although Nasef et al suggest that a purified Stro-1-enriched population augment the suppressive effect in allogeneic transplantation, Murphy et al showed that allogeneic endometrial regenerative cells (ERC or menstrual blood mesenchymal stem cells), that are Stro-1 negative, were efficient for the treatment of critical limb ischemia in rats [34,32]. In accordance to recent studies in human endometrium, htMSCs are also Stro1 negative [35].…”
Section: Multilineage Differentiation In Vitromentioning
confidence: 65%
“…Treatments with GSK-3β inhibitors and C1q also increase MMP expression in MSCs, which are important for the degradation of the basement membrane during extravasation [60,101] . A combination of the haematopoietic growth factors erythropoietin (EPO) and granulocyte colony stimulating factor (G-CSF) has also been reported Integrin αv [85] BM [85] Yes [85] Yes [85] Integrin β1 [11,[86][87][88] BM [11,[86][87][88] Yes [11,[86][87][88] CB [86,87] AT [86][87][88] Skin [87] Integrin β3 [85] BM [85] Yes [85] Yes [85] Integrin β4 [85] BM [85] Yes [85] Yes [85] ALCAM [17,87] BM [87] Yes [17] AT [87] CB [17,87] Proteases MMP-1 [90] BM [90] Yes [90] Yes [90] In vitro migration [90] MMP-2 [65,68,74,…”
Section: Pretreatment or Priming Of Mscs In Culture Or Modifying The mentioning
confidence: 99%
“…There is great interest in using these cells in a wide variety of clinical domains, such as Neurology, Orthopaedics, Cardiology and Haematology [3][4][5][6] . This interest arises from the following MSC characteristics: They have immunomodulatory capacities, they are multipotent and are thus possible effectors for tissue regeneration, and they tend to migrate to sites of tissue injury/inflammation [7][8][9][10][11] . Additionally MSCs might escape immune recognition, although conflicting observations about this particular phenotype have been published.…”
Section: Introductionmentioning
confidence: 99%
“…One pathway by which TGFβ exerts its anti-proliferative effect on T lymphocytes is through blockade of the production of the T-cell mitogenic cytokine IL-2 [34]. TGFβ also inhibits cell proliferation through controlling the expression of cell cycle regulators, including up-regulation of cyclin-dependent kinase inhibitors (CKIs) p15, p21 and p27 and down-regulation of cell cycle-promoting factors, such as c-myc, cyclin D2 and cyclin E [35].…”
Section: Transforming Growth Factor Beta (Tgf-β)mentioning
confidence: 99%